Biomaterials for direct cardiac repair-A rapid scoping review 2012-2022 - Sedláková, Veronika; Mourcos, Sophia; Pupkaitė, Justina; Lunn, Yvonne; Visintini, Sarah; Guzman-Soto, Irene; Ruel, Marc; Suuronen, Erik; Alarcon, Emilio I (Acta biomaterialia, 2024)
A plethora of biomaterials for heart repair are being tested worldwide for potential clinical application. These therapeutics aim to enhance the quality of life of patients with heart disease using various methods to improve cardiac function. Despite the myriad of therapeutics tested, only a minority of these studied biomaterials have entered clinical trials. This rapid scoping review aims to analyze literature available from 2012 to 2022 with a focus on clinical trials using biomaterials for direct cardiac repair, i.e., where the intended function of the biomaterial is to enhance the repair of the endocardium, myocardium, epicardium or pericardium. This review included neither biomaterials related to stents and valve repair nor biomaterials serving as vehicles for the delivery of drugs. Surprisingly, the literature search revealed that only 8 different biomaterials mentioned in 23 different studies out of 7038 documents (journal articles, conference abstracts or clinical trial entries) have been tested in clinical trials since 2012. All of these, intended to treat various forms of ischaemic heart disease (heart failure, myocardial infarction), were of natural origin and most used direct injections as their delivery method. This review thus reveals notable gaps between groups of biomaterials tested pre-clinically and clinically. STATEMENT OF SIGNIFICANCE: Rapid scoping review of clinical application of biomaterials for cardiac repair. 7038 documents screened; 23 studies mention 8 different biomaterials only. Biomaterials for repair of endocardium, myocardium, epicardium or pericardium. Only 8 different biomaterials entered clinical trials in the past 10 years. All of the clinically translated biomaterials were of natural origin.
Keywords: Animals; Biocompatible Materials; lidé; biokompatibilní materiály; Humans; zvířata